Enhancement Concentration of Bioethanol Through Packed Sieve Tray Distillation - Taufany, Fadlilatul; Putra, Pranata Adi; Nuringtyas, Rydho Jalu (IPTEK Journal of Proceedings Series, 2015)
Bioethanol is one of alternative renewable energy that can be produced by distillation process. Distillation itself is a method of separation and purification that most widely used in the chemical industry. Nowadays, distillation equipment that is commonly used in the industry is sieve tray tower due to its affordable in cost and simplicity in design. Its performance can be improved by the addition of packing on the tray can improve efficiency. This study aims to evaluate the performance of the developed steel wool packing in sieve tray distillation with regards to the bioethanol purity. Our results showed that the addition of the developed packing in each tray significantly increased the concentration of ethanol up to 99.5%